2017
DOI: 10.1016/j.reprotox.2017.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Herbal laxatives and antiemetics in pregnancy

Abstract: a b s t r a c tConstipation appears in the 2nd and 3rd trimester of pregnancy, while nausea is the strongest in the 1st trimester. This review summarizes the applicability of herbal laxatives and antiemetics in pregnancy.A human study has shown that flax oil as laxative is safe from 2nd trimester. Human data is not available about the rhubarb, but animal studies reveal that its emodin content induces fetal abnormalities. Fenugreek induces teratogenic malformation both in human and animals. Senna seed is proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Perinatal exposure of goats at the early pregnancy caused fetal death and reabsorption. And high dose–induced tissue damage in the mother (vacuolation of liver cells and kidneys) and myocardium bone necrosis (Samavati, Ducza, Hajagos‐Tόth, & Gaspar, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perinatal exposure of goats at the early pregnancy caused fetal death and reabsorption. And high dose–induced tissue damage in the mother (vacuolation of liver cells and kidneys) and myocardium bone necrosis (Samavati, Ducza, Hajagos‐Tόth, & Gaspar, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Aqueous extract of fenugreek was demonstrated to have potential teratogenic effects in humans and animals, and seed consumption during pregnancy has been associated with a range of congenital malformations, including hydrocephalus, anencephaly, and spina bifida. (Khalki, M'hamed, Bennis, Chait, & Sokar, 2010; Samavati et al, 2017). Prenatal exposure of mice to a high dose of fenugreek seeds caused growth retardation and altered neurobehavioral performance in the postweaning period (Khalki, Bennis, Sokar, & Ba‐M'hamed, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Again, these findings were consistent with those reported in a previous study in which pregnant women and gynecologists agreed that the risks of abortion associated with using ginger for nausea and vomiting of pregnancy should be addressed during clinical consultations [ 15 ]. Previous studies showed that aqueous extract of fenugreek had potential teratogenic effects in humans and animals [ 33 , 39 ]. Health regulatory bodies tend to recommend avoidance of herbal remedies even when the risks associated with their use are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Many breastfeeding women could be asthmatics and should be warned of this potential harm of using fenugreek. Again, breastfeeding women should be warned that fenugreek could cause nausea and vomiting which could be disturbing to the breastfeeding women and could have negative effects on their reported quality of life [ 39 ]. Fenugreek could be associated with diarrhea and excessive sweating for the breastfeeding women and their breastfed infants [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of fenugreek ( Trigonella foenum graecum ) in pregnancy may induce congenital malformations and death [133,134]. In male rats, mice, and rabbits, fenugreek may induce testicular toxicity and anti-fertility effects, while it alters fertility, implantation, and abortions in females [134].…”
Section: Development: Pregnancy Lactation and Developmental Trajmentioning
confidence: 99%